Evaluasi Sistem Penyanggaan pada Tunnel THC 04 CV Tahiti Coal Menggunakan Klasifikasi RMR - Wahyu Marta Novri; Bambang Heriyadi (Departemen Teknik Pertambangan FT UNP, 2021)
Excavation of tunnels in underground mines is a fairly complex job, because it will result in changes in the balance of rock conditions that can cause failure. Therefore, a good geotechnical analysis is needed to provide proper treatment of the excavated rock.Based on the results of laboratory test, physical properties for siltstone is an average natural density of 2,4 gr/cm3 and for coal is an average natural density of 1,24 gr/cm3, and mechanical properties of PLI for siltstone is an average of 1,4 MPa and for coal is an average of 0,45 MPa. From the result of the Bieniawski-1989 RMR analysis, the rocks on the roof and the wall has a value of 54 and include to rock mass class III. RMR 54 has stand up time 37 days to 3 m of span. Based on the analysis using Cemal Biron theory in 1983, the value of stress to the cap is 528,06 kg/cm2, side post is 170,19 kg/cm2, the wood clearance stress is 623,75 kg/cm2, and the wood compressive strength is 368,75 kg/cm2. The FS of cap is using 20 cm diametre of wood is 1.18, and the FS of side post is using 23 cm diametre of wood is 2,17. To make the FS stable on cap side, it needs to upgrade the size of the wood to at least 22 cm of diametre, so the FS would be 1,57 (declared safe), or reduce the distance of the support system to maximum of 1,15 m.